Prevalence and association of self-medication practices with personal and educational factors among university employees of Saudi Arabia: A cross-sectional study - Syed Shahid Habib; Thamir Al-khlaiwi; Abdullah Almushawah; Abdulaziz Alsomali; Abdulrahman Abdulaziz A. Bin Ateeq; Faisal Abdulkader Aljarrah; Saleh Husam Aldeligan; Faisal Soud Alfwzan; Syed Abubakar Habib; Syed Mohammad Habib (Journal of Family Medicine and Primary Care)
Background and Objective: Self-medication (SM) is an emerging practice in both developing and developed countries. The commonality of this behavior is observed in patients with specific environments. The current study endeavored to determine the prevalence of SM practices and their correlated factors among academic employees in Saudi Arabia. Methods: A cross-sectional study was conducted at King Saud University Hospital, recruiting 383 participants. The participants received an online survey on self-medication practices. The data were analyzed using descriptive statistics and regression analysis. Results: In the study, all the participants reported practicing SM at least one time. Of those who practiced SM, 66.7% (102) were unmarried with a significant difference (P = 0.036) while 68.0% (117) had no children (P = 0.003). Non-Government employees and unemployed participants had the highest percentage of experiencing SM (70.5%, n = 31, P = 0.036). Our results reveal that health perceiving, life satisfaction, and religious reasons were not significantly associated with practicing SM with P value = 0.704, 0.535, and 0.482, respectively. In the univariate model, gender, marital status, and the number of children revealed a significant correlation with SM (P value = 0.136, 0.058, and 0.040), respectively. SM was 1.4 times as likely if the participant was female and 1.3 if the participant was unmarried. The multivariate regression model shows that gender and marital status lost their significance while number of children (P = 0.023) was significantly correlated with SM. Our results also show the main reasons for self-medication were prior knowledge (25%), time-consuming consultations (21.6%), the belief that the condition did not require a doctor (22.4%), and previous experience with similar symptoms (23%) while major causative clinical conditions involved in SM is pain (37.5%) and fever (28.4%). It also shows that 33% experienced no side effects and 34% experienced shortness of breath as a side effect of practicing SM. Conclusion: Our study spotted a significant frequency of SM behavior with high prevalence among University employees. Our study shows that gender, marital status, and number of children have a significant correlation with SM. The pharmacist’s role is pivotal in promoting awareness for the safe utilization of over-the-counter drugs, and their proactive engagement is paramount. Educational health programs should be implemented to minimize SM malpractice.